Complementation in trans of Porphyromonas gingivalis Lipopolysaccharide Biosynthetic Mutants Demonstrates Lipopolysaccharide Exchange - Glew, Michelle D. (J Bacteriol, 2021)
Porphyromonas gingivalis, a bacterial pathogen contributing to human periodontitis, exports and anchors cargo proteins to its surface, enabling the production of black pigmentation using a type IX secretion system (T9SS) and conjugation to anionic lipopolysaccharide (A-LPS). To determine whether T9SS components need to be assembled in situ for correct secretion and A-LPS modification of cargo proteins, combinations of nonpigmented mutants lacking A-LPS or a T9SS component were mixed to investigate in trans complementation. Reacquisition of pigmentation occurred only between an A-LPS mutant and a T9SS mutant, which coincided with A-LPS modification of cargo proteins detected by Western blotting and coimmunoprecipitation/quantitative mass spectrometry. Complementation also occurred using an A-LPS mutant mixed with outer membrane vesicles (OMVs) or purified A-LPS. Fluorescence experiments demonstrated that OMVs can fuse with and transfer lipid to P. gingivalis, leading to the conclusion that complementation of T9SS function occurred through A-LPS transfer between cells. None of the two-strain crosses involving only the five T9SS OM component mutants produced black pigmentation, implying that the OM proteins cannot be transferred in a manner that restores function and surface pigmentation, and hence, a more ordered temporal in situ assembly of T9SS components may be required. Our results show that LPS can be transferred between cells or between cells and OMVs to complement deficiencies in LPS biosynthesis and hemin-related pigmentation to reveal a potentially new mechanism by which the oral microbial community is modulated to produce clinical consequences in the human host. IMPORTANCE Porphyromonas gingivalis is a keystone pathogen contributing to periodontitis in humans, leading to tooth loss. The oral microbiota is essential in this pathogenic process and changes from predominantly Gram-positive (health) to predominantly Gram-negative (disease) species. P. gingivalis uses its type IX secretion system (T9SS) to secrete and conjugate virulence proteins to anionic lipopolysaccharide (A-LPS). This study investigated whether components of this secretion system could be complemented and found that it was possible for A-LPS biosynthetic mutants to be complemented in trans both by strains that had the A-LPS on the cell surface and by exogenous sources of A-LPS. This is the first known example of LPS exchange in a human bacterial pathogen which causes disease through complex microbiota-host interactions.